A novel approach to pulmonary bronchial tree model construction and performance index study - Liu, Yang; Qiu, Weiyan; Li, Longyu; Chen, Rongchang; Kang, Yan; Ruan, Shuangchen (Frontiers in Pharmacology, 2023)
The demand for respiratory disease and dynamic breathing studies has continuously driven researchers to update the pulmonary bronchial tree's morphology model. This paper aims to construct a bronchial tree morphology model efficiently and effectively with practical algorithms. Next, we build a performance index system using failure branch rate, volume ratio, and coefficient of variation of terminal volumes to evaluate the model performance. We optimized the parameter settings and found the best options to build the morphology model, and we constructed a 14-generations bronchial tree model with a decent performance index. The dimensions of our model highly match the published data from anatomic in-vitro measurements. The proposed model is adjustable and computable, which will be used in future dynamic breathing simulations and respiratory disease studies.